The telomere lengthening conundrum – it could be biology - Bateson, Melissa (Aging Cell, 2016)
Longitudinal studies of human leucocyte telomere length often report a percentage of individuals whose telomeres appear to lengthen. However, based on theoretical considerations and empirical data, Steenstrup et al. (Nucleic Acids Research, 2013, vol 41(13): e131) concluded that this lengthening is unlikely to be a real biological phenomenon and is more likely to be an artefact of measurement error. We dispute the logic underlying this claim. We argue that Steenstrup et al.'s analysis is incomplete because it failed to compare predictions derived from assuming a scenario with no true telomere lengthening with alternative scenarios in which true lengthening occurs. To address this deficit, we built a computational model of telomere dynamics that allowed us to compare the predicted percentage of observed telomere length gainers given differing assumptions about measurement error and the true underling dynamics. We modelled a set of scenarios, all assuming measurement error, but both with and without true telomere lengthening. We found a range of scenarios assuming some true telomere lengthening that yielded either similar or better quantitative fits to the empirical data on the percentage of individuals showing apparent telomere lengthening. We conclude that although measurement error contributes to the prevalence of apparent telomere lengthening, Steenstrup et al.'s conclusion was too strong, and current data do not allow us to reject the hypothesis that true telomere lengthening is a real biological phenomenon in epidemiological studies. Our analyses highlight the need for process‐level models in the analysis of telomere dynamics.